2014
DOI: 10.1155/2014/618109
|View full text |Cite
|
Sign up to set email alerts
|

The Design of an Urban Roadside Automatic Sprinkling System: Mitigation of PM2.5–10 in Ambient Air in Megacities

Abstract: The objective of this research paper is to describe the system architecture for an urban roadside automatic mist-generating system. Its primary purpose is to mitigate particulate matter especially PM2.5–10. In this paper, four graphs are provided to exhibit the constituent elements of this system. This paper also discusses the functional extensions of this system for alternative uses in civil engineering which include winter road deicing and desnowing with added salt; clean-up of street dust; lowering of tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Water spray (from sprinkler on road or atop a tall building) to simulate natural types of precipitation has been proposed as an important abatement strategy to facilitate the reduction of ambient PM concentrations (including trace elements) in urban China (Liu et al, 2014;Yu, 2014). However, several field measurements revealed that water spray activities did not influence the PM mass levels (e.g., Karanasiou et al, 2012;Karanasiou, 2014).…”
Section: Precipitation Effectmentioning
confidence: 99%
“…Water spray (from sprinkler on road or atop a tall building) to simulate natural types of precipitation has been proposed as an important abatement strategy to facilitate the reduction of ambient PM concentrations (including trace elements) in urban China (Liu et al, 2014;Yu, 2014). However, several field measurements revealed that water spray activities did not influence the PM mass levels (e.g., Karanasiou et al, 2012;Karanasiou, 2014).…”
Section: Precipitation Effectmentioning
confidence: 99%
“…Roadside sprinklers are used in several megacities in China to combat air pollution, and a significant reduction in PM 2.5 concentrations has been noted through field monitoring [99]. In another study, an automated roadside sprinkling system was developed to suppress dust suspension and mitigate ambient PM, and it achieved a 95-100% reduction efficiency [100]. A sprinkler can be used to achieve other objectives too.…”
Section: Roadside Sprinklers-an Analogymentioning
confidence: 99%
“…A sprinkler can be used to achieve other objectives too. For example, it was used to generate fresh or salty water mist for the inactivation of airborne influenza viruses in winter, as the survivability of the viruses decreased with absolute humidity [100]. It was also used to spray salty water in winter to de-ice and de-snow roads, and a mist in summer to cool down the air [101].…”
Section: Roadside Sprinklers-an Analogymentioning
confidence: 99%
“…Although these particles are difficult to mitigate since they are not products of tailpipe emissions, there are different control mechanisms that could be used to effectively reduce the airborne dust emissions as well as the suspended dust on the paved/unpaved roadside [28][29][30][31][32][33][34]. Among all, one of the most effective, but expensive, methods to remove the non-tailpipe emissions from the vehicles in roadways is the automatic mist-generating systems (i.e., water sprinkling), in which spraying of water via pressurized nozzles prevents the formation of airborne dust particles [29,30]. In addition, there are mechanical and chemical methods to remove the suspended dust from roadside, including the use of dust suppressants, water flushing, and street sweeping, which are mostly used by municipalities [28].…”
Section: Introductionmentioning
confidence: 99%